PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT ISTANA CITRA INDAH - Tio, Donly; Rustam, Triana Ananda (SCIENTIA JOURNAL, 2021)
Human resources is an important aspect for company's sustainability. Without human resources, an industry definitely cannot be operated properly. Therefore, human resources must be managed properly to increase the employee's productivity. A good human resources management also reflect the company's capability. The goal of this research is to find out the effect of motivation and work discipline to employee's performance in PT Istana Citra Indah that has about 108 employees. This research using statistical data analysis method by using SPSS Version 26 to get the significant results. The results of multiple regression shows that the variables of motivation and work discipline affect significantly positive to employee's performance based on the results of the regression equation and the value of R Square. Based on statistical data, the indicators that used in this research is valid and reliable. The hypothesis test in this research using T-Test that show motivation variable and work discipline affect significantly to employee's performance variable. Through the F-Test it shows that the variables of motivation and work discipline affect simultaneously to the employee's performance variable with the F Value is greater than the F Table.